Pengaruh Latihan Triangel Terhadap Ketepatan Passing Ekstrakurikuler Futsal SMK Muhammadiyah 2 Kuningan - Nugraha, Adia Hidayat; Dwi, Dicky Reva Apriana Sanga (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Effect of Triangel Training on the Accuracy of Passing in Futsal Players of SMK Muhammadiyah 2 Kuningan, Physical Education and Recreation Study Program (PJKR). This study aims to determine the influence of the triangle training method on the accuracy of passing in futsal players of Smk Muhammadiyah 2 Kuningan. The subject of this study is students who were selected to participate in futsal at SMK Muhammadiyah 2 Kuningan. The population in this study is all futsal players of SMK Muhammadiyah 2 Kuningan. The sampling technique used is total sampling, which amounts to 20 0rang. The research method that the author uses to test the correctness of the hypothesis that has been proposed is the experimental method. The instrument used in this study is the passing accuracy test. The data analysis used is a quantitative descriptive test and a t-test. The results of this study showed that the triangel training method on the accuracy of the pass in extracurricular futsal players of SMK Muhammadiyah 2 Kuningan was 30.45%